Adult-onset Still's disease in focus: Clinical manifestations, diagnosis, treatment, and unmet needs in the era of targeted therapies - Efthimiou, Petros; Kontzias, Apostolos; Hur, Peter; Rodha, Kavita; Ramakrishna, G S; Nakasato, Priscila (Seminars in arthritis and rheumatism, 2021)
•AOSD is a rare multisystem inflammatory disease characterized by spiking high fevers, arthritis or arthralgia, maculopapular salmon-colored rash, neutrophilic leukocytosis, and hyperferritinemia.•Emerging evidence suggest that AOSD and SJIA are part of the same disease continuum with different ages of onset.•Owing to an increased awareness about AOSD, incidence and prevalence rates have increased over time.•AOSD may present with different phenotypes, one with prominent systemic features and one with chronic arthritis.•There is no specific test for diagnosis of AOSD, but classification criteria are available.•In the absence of timely diagnosis and appropriate management, AOSD can lead to irreversible joint damage with functional impairment and potentially life-threatening complications.•There are no internationally recognized guidelines for the management of AOSD, although local guidelines have been developed recently in Japan and Italy.•Currently, biologic drugs are usually reserved for patients who do not respond to conventional DMARDs. Further studies are needed to assess if early treatment with biologics leads to better patient outcomes and a change in the natural history of AOSD.•Treatment with IL-1 inhibitors in AOSD patients refractory to conventional treatment can lead to clinical remission.•Canakinumab is the only FDA-approved biologic for AOSD in the USA; canakinumab and anakinra are approved in Europe. Adult-onset Still's disease (AOSD) is a rare systemic inflammatory disorder of unknown etiology, characterized by a clinical triad of high spiking fever, arthralgia (± arthritis), and evanescent skin rash. Management of AOSD poses several challenges, including difficulty in diagnosis and limited therapeutic options. In this review, we examined whether AOSD and systemic juvenile idiopathic arthritis (SJIA) represent a continuum of the same disease. We also explored the latest available evidence related to prevalence, clinical and laboratory manifestations, complications, diagnostic challenges, novel biomarkers, and treatment options in the era of biologics and identified the unmet needs of patients with AOSD. A comprehensive systematic literature search was performed in the Embase and MEDLINE (via PubMed) literature databases. The search was limited to human studies published in English from inception up to March 2020. Additionally, abstracts presented at various conferences were screened and hand searches were performed. Publications were processed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A total of 123 publications were identified through the literature search, majority of which were case series and retrospective observational studies. AOSD and SJIA are widely considered part of the same disease spectrum owing to similarities in their clinical and biological features. The clinical presentation of AOSD is highly variable, accompanied by a broad spectrum of disease manifestations. Recent evidence suggests that the AOSD disease course can be classified into two distinct categories: “systemic” and “articular.” Furthermore, AOSD patients may experience various life-threatening complications, such as macrophage activation syndrome — reported in as high as 23% of AOSD patients and considered to be the most severe complication characterized by a high mortality rate. The ambiguity in presentation and lack of serologic markers make the diagnosis of AOSD difficult, often leading to a delay in diagnosis. Given these limitations, the Yamaguchi and Fautrel criteria are the most widely used diagnostic tools in clinical practice. It has been observed that a clinical diagnosis of AOSD is generally reached by exclusion while investigating a patient with fever of unknown origin. Recent advances have demonstrated a major role of proinflammatory cytokines, such as interleukin (IL)-1, IL-6, IL-18, and IL-37, and other biomarkers in the pathogenesis and management of AOSD. Owing to the rarity of the disease, there are very limited clinical trials evaluating management strategies for AOSD. The current AOSD treatment paradigm includes non-steroidal anti-inflammatory drugs (NSAIDs) and glucocorticoids initially, conventional synthetic disease-modifying anti-rheumatic drugs in steroid-refractory patients, and biologics in those resistant to conventional treatment. Only a few country-specific guidelines for the management of AOSD have been published, and a treat-to-target approach, as previously recommended for SJIA, is still lacking. Canakinumab is the only FDA–approved biologic for the treatment of AOSD. Emerging evidence supports that AOSD and SJIA represent a continuum of the same disease entity. Despite advancements in the understanding of AOSD, it continues to pose a substantial burden on patients and the healthcare systems, and substantial unmet needs exist across key domains such as the pathway to diagnosis, use of biomarkers in clinical practice, and standardized treatment strategies. Further research and collaboration is crucial for optimizing the diagnosis and management of AOSD patients.